Superconductivity above 80 K in polyhydrides of hafnium. (October 2022) - Zhang, C.L.; He, X.; Li, Z.W.; Zhang, S.J.; Min, B.S.; Zhang, J.; Lu, K.; Zhao, J.F.; Shi, L.C.; Peng, Y.; Wang, X.C.; Feng, S.M.; et al.
Abstract: Studies on polyhydrides are attracting growing attentions recently due to their potential high temperature superconductivity (SC). We here report the discovery of SC in hafnium polyhydrides at high pressures. The hafnium superhydrides are synthesized at high pressure and high temperature conditions using diamond anvil cell in combination with in-situ high pressure laser heating technique. The SC was investigated by in-situ high pressure resistance measurements in applied magnetic fields. A superconducting transition with onset T c ∼83 K was observed at 243 GPa. The upper critical field μ 0 H c2 ( 0 ) was estimated to be 24 T by GL theory and the consequent superconducting coherent length ξ to be ∼37 Å. Our results suggest that the superconducting phase is from C 2/ m -HfH14 . This is the first 5 d transition metal polyhydride superconductor with T c above the liquid nitrogen temperature. Graphical abstract: Image 1 Highlights: Searching for high temperature superconductivity is of great interest both for fundamental science & potential applications. Although some hydrides are observed to be superconductors there is no report of high Tc superconductor for 5d transition element hydrides. Here we report discovery of superconductivity in hafnium polyhydrides synthesized at high pressure & high temperature. Superconductivity above 83K was achieved in hafnium polydrides that is the record high for transition metal hydrides.